Kebijakan MBKM Santri Dalam Upaya Peningkatan Mutu Kinerja Wali Asuh Pondok Pesantren Nurul Jadid - Dini Hanifiyah (CV Edujavare Publishing, 2024)
Article This aim For know curriculum policy for the Independent Learning Campus (MBKM) for Santri Students in its efforts to improve the quality of the performance of foster carers at the Nurul Islamic boarding school. Several Islamic boarding school policies are certainly one of the efforts to improve this, according to the Independent Learning MBKM Santri Independent Campus policy which was launched at Nurul Jadid. This Islamic boarding school curriculum development policy is an effort to provide opportunities for foster carers with student status to receive compensation in the form of course conversions according to MKBM regulations. This is given priority to guardians (students who have the status of Islamic boarding school students and are administrators at the Nurul Jadid Islamic Boarding School. This research use approach qualitative with study literature (library research) as a related technical analysis with discussion This . Results from writing This elaborate that The MBKM curriculum policy at Nurul Jadid University is santri-based as a policy for Islamic boarding schools and Islamic boarding school campuses and is a reference for programs in efforts to improve the performance of foster carers by converting grades as compensation for teaching at Islamic boarding schools.